Preliminary Result in Endoscopic Video Assisted Breast Surgery - Randi Dwiyanto; Kristanto Yuli Yarso (HM Publisher, 2021)
Background : The development of technology has grown rapidly in surgical science, especially the use of endoscopy to develop operations in producing minimal scar tissue. Endoscopic VABS is a surgical technique and began to develop since 1995. The technique has several approaches, namely through the chest wall, mammary and axilla. The descriptive study aims to report our first experience in the management of benign breast tumors with Endoscopic Video Assisted Breast Surgery. Methods : Ten patients with benign breast tumor have performed Endoscopic VABS in the period March 2017 to September 2017 at the Hospital in Surakarta. The largest diameter at the nodule, duration of operation, length of postoperative care, postoperative pain, cosmetic outcomes and complications were observed retrospectively. Result : All patients are women with median age 28 years. The largest diameter that can be taken is 3.5 cm with median 2 cm. One patient performed the conversion into a lumpectomy with conventional techniques due to difficult dissection and uncontrolled bleeding. The median duration of surgery was 60 minute with an average length of treatment for 2 days postoperatively. Average VAS Score was 4. No postoperative complications were found. But cosmetically, all patients are satisfied with the results of surgical wounds. Conclusion : The VABS endoscopic procedure is safe and effective procedure and has excellent cosmetic benefits because it does not show scar tissue in the breast area. This VABS Endoscopic technique has a weakness in terms of longer duration of operation compared to conventional techniques, but this can be overcome with the expertise and experience of the operator.